Aspergillus flavus growth inhibition by Lactobacillus strains isolated from traditional fermented Kenyan milk and maize products - Ahlberg, Sara H.; Joutsjoki, V.; Laurikkala, S.; Varmanen, P.; Korhonen, H. (Springer, 2017)
Certain strains of lactic acid bacteria have been reported to inhibit fungal growth and may so be potential as biocontrol agents. In this study, 171 LAB strains were isolated from traditional fermented Kenyan milk and maize products and tested against aflatoxin-producing A. flavus fungi. The three LAB strains showing highest antifungal activity were identified as Lactobacillus plantarum. None of the strains were able to completely inhibit fungal growth under conditions favorable for fungi and suboptimal for LAB. These conditions probably reduced the growth and metabolic activity of some LAB isolates, as several growth-related aspects like production of antifungal biomolecules and other metabolites contribute to the inhibiting activity. The results suggest that certain LAB strains could be employed in food to control the growth of aflatoxigenic fungi. Further studies to establish the efficacy of the potential LAB strains in fermented products are in progress.